Summons of Registered Letters in Civil Procedure Law of Religious Courts: A Study of Legal Certainty and Substantive Justice Theory in the Perspective of Islamic Studies - Hariyadi, Luqman; Sumbulah, Umi; Sugiyar, Sugiyar (Rechtsvinding, 2025)
This article examines summons by registered mail in civil cases before Indonesia’s Religious Courts as a critical intersection between legal certainty, legal protection, and substantive justice from an Islamic Studies perspective. The issue is crucial because summons determine whether a party’s right to know, to appear, and to be heard is effectively secured. At the same time, judicial digitalisation and cooperation with the national postal service (PT Pos Indonesia) have significantly altered the traditional bailiff-based model. The aims of this study are: (1) to describe the normative configuration and practical implementation of registered-mail summons in the Religious Courts; (2) to assess them through the Theory of Legal Certainty and Philipus M. Hadjon’s Theory of Legal Protection; and (3) to interpret their implications for substantive justice in Islamic Studies. This research employs a qualitative, normative-juridical Design, combined with an Islamic Studies approach, based on library research, statutory, conceptual, and case approaches, and using content, discourse, and interpretive analysis. The findings indicate that registered-mail summons enhances procedural certainty but does not fully guarantee legal protection or substantive justice due to problems with identity, addresses, postal SOPs, and the cost burden of summons. The article argues for a reconstructed susummoDesigning with maligned aqāṣid al-sharī'ah and the principles of simple, swift, and low-cost justice.